The role of macrophages in hypertrophic scarring: molecular to therapeutic insights - Shen, Lele; Zhou, Yao; Gong, Jie; Fan, Hongqiao; Liu, Lifang (Frontiers in Immunology, 2025)
Hypertrophic Scar (HS) is a common fibrotic disease of the skin, usually caused by injury to the deep dermis due to trauma, burns, or surgical injury. The main feature of HS is the thickening and hardening of the skin, often accompanied by itching and pain, which seriously affects the patient’s quality of life. Macrophages are involved in all stages of HS genesis through phenotypic changes. M1-type macrophages primarily function in the early inflammatory phase by secreting pro-inflammatory factors, while M2-type macrophages actively contribute to tissue repair and fibrosis. Despite advances in understanding HS pathogenesis, the precise mechanisms linking macrophage phenotypic changes to fibrosis remain incompletely elucidated. This review addresses these gaps by discussing the pathological mechanisms of HS formation, the phenotypic changes of macrophages at different stages of HS formation, and the pathways through which macrophages influence HS progression. Furthermore, emerging technologies for HS treatment and novel therapeutic strategies targeting macrophages are highlighted, offering potential avenues for improved prevention and treatment of HS.